2022
DOI: 10.1186/s12891-022-05427-1
|View full text |Cite
|
Sign up to set email alerts
|

Association of bone-related biomarkers with femoral neck bone strength

Abstract: Background Femoral neck fractures are the worst consequence of osteoporosis (OP), and its early prevention and treatment have become a public health problem. This study aims to investigate the relationship of bone-related biomarkers, femoral neck bone mineral density (BMD) and maximum load (Lmax), selecting the indicator which can reflect femoral neck bone loss and reduced bone strength. Methods A total of 108 patients were recruited from January 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 31 publications
(31 reference statements)
0
7
0
Order By: Relevance
“…Consequently, researchers have been seeking alternative methods to diagnose osteoporosis and evaluate the risk of osteoporotic fractures without using a DXA examination. Recently, the FRAX (Fracture Risk Assessment Tool) score, which improves fracture prediction beyond that based on BMD measurement alone, has been widely used 20 . Other measures, such as hand grip strength and anthropometric measurements such as calf circumference, have also been introduced to diagnose BMD cost-effectively 16,21,22 .…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, researchers have been seeking alternative methods to diagnose osteoporosis and evaluate the risk of osteoporotic fractures without using a DXA examination. Recently, the FRAX (Fracture Risk Assessment Tool) score, which improves fracture prediction beyond that based on BMD measurement alone, has been widely used 20 . Other measures, such as hand grip strength and anthropometric measurements such as calf circumference, have also been introduced to diagnose BMD cost-effectively 16,21,22 .…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that when VDR expression levels are downregulated, BMD and t -score decreased proportionally, associating the altered VDR expression pattern with a gradual stratification of bone densitometry, from the healthy to severe OP phenotype. A strength of our analysis is undoubtedly the presence of patients with severe OP, defined by the coexistence of the disease together with fragility fractures, particularly at the femur site [ 39 ]. Confirming the negative role played by the VDR decrease in OP pathogenesis and fracture risk, our results showed lower mean VDR expression levels in patients with femur fractures (OP_FF), which is considered the index fracture of OP disease.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we also correlated the methylation status of a CpG island located in the VDR promoter region with the VDR gene expression levels with no significant results. Several studies have highlighted the role of methylation in modulating VDR expression in different pathological contexts, mainly in autoimmune diseases, but none of these has concerned OP [ 39 ]. We focused our methylation analysis in a small region including six CG sites located in a VDR promoter CpG island (CGI 1062) already shown to functionally modulate VDR expression in a South African population [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we suggest that the AGEs level as a correction factor that could improve the capacity of FRAX algorithm to predict fracture risk in T2D postmenopausal women. Serum bone turnover markers can be used to assess bone loss or formation more sensitive than BMD (53)(54)(55). Previous studies demonstrated reduced bone resorption and formation in T2D individuals (56-58), suggesting that hyperglycemia and AGEs crosslinking may impair the function of osteoblasts and osteoclasts, thereby inhibiting bone formation and promoting bone resorption.…”
Section: Discussionmentioning
confidence: 99%
“…Serum bone turnover markers can be used to assess bone loss or formation more sensitive than BMD ( 53 55 ). Previous studies demonstrated reduced bone resorption and formation in T2D individuals ( 56 58 ), suggesting that hyperglycemia and AGEs crosslinking may impair the function of osteoblasts and osteoclasts, thereby inhibiting bone formation and promoting bone resorption.…”
Section: Discussionmentioning
confidence: 99%